2020
DOI: 10.1038/s41598-020-58196-z
|View full text |Cite
|
Sign up to set email alerts
|

Low-frequency variability in photoplethysmographic waveform and heart rate during on-pump cardiac surgery with or without cardioplegia

Abstract: We studied the properties of low-frequency (LF) heart rate variability (HRV) and photoplethysmographic waveform variability (PPGV) and their interaction under conditions where the hemodynamic connection between them is obviously absent, as well as the LF regulation of PPGV in the absence of heart function. The parameters of HRV and finger PPGV were evaluated in 10 patients during cardiac surgery under cardiopulmonary bypass (on-pump cardiac surgery) with or without cardioplegia. The following spectral indices … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 36 publications
1
22
0
4
Order By: Relevance
“…However, some experimental results 44 suggest the functional independence of the LF oscillations in RR-intervals and PPG. Earlier, we also observed the phenomenon of the synchronization between the LF oscillations in RR-intervals and PPG 30,33,48 . Typically, the intervals of synchronization are alternating with the intervals of the desynchronized behavior.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…However, some experimental results 44 suggest the functional independence of the LF oscillations in RR-intervals and PPG. Earlier, we also observed the phenomenon of the synchronization between the LF oscillations in RR-intervals and PPG 30,33,48 . Typically, the intervals of synchronization are alternating with the intervals of the desynchronized behavior.…”
Section: Discussionsupporting
confidence: 52%
“…It is known that PPG allows indirect estimation of the frequency properties of arterial pressure variability (APV), since PPG signal is influenced to a strong degree by oscillations of AP 31 . Also, we demonstrated a perspective clinical application of LF oscillation synchronization to the estimation of fatal cardiovascular risk after myocardial infarction 32,33 , and to the personalization of medical therapy for myocardial infarction patients 34 and hypertensive patients 35 .…”
mentioning
confidence: 99%
“…We have proposed a mathematical model that allows one to simulate the heart rate variability and arterial pressure oscillations under the influence of respiration and autonomic control loops. Earlier, it was shown that taking into account the non-linear properties and self-oscillatory dynamics of these loops it is possible to explain the experimentally observed complex chaotic dynamics of the heart rate and synchronization processes within the CVS ( Ringwood and Malpas, 2000 ; Prokhorov et al, 2003 ; Karavaev et al, 2009 , 2016 , 2019 ; Kiselev et al, 2016a , 2020 ). In the present paper, a modified model is proposed that takes into account the influence of the activity of the cerebral cortex on autonomic control in the states of sleep and wakefulness.…”
Section: Discussionmentioning
confidence: 99%
“…As well as our earlier models, it reproduces the pathological changes that lead to arterial hypertension ( Karavaev et al, 2016 ), reaction to the passive orthostatic test ( Ishbulatov et al, 2018 ), and reaction to the autonomic blockade due to administration of Arfonad ( Karavaev et al, 2016 ). Moreover, the model simulates the chaotic dynamics of heart rate ( Karavaev et al, 2019 ) and phase synchronization between the autonomic control loops ( Ishbulatov et al, 2017 ), which is observed in humans ( Bartsch et al, 2012 ) and is important for diagnostics and understanding of some circulatory diseases ( Prokhorov et al, 2003 ; Kiselev et al, 2016a , b , 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The results of the studies showed significant correlations between HRV and fMRI data (C. . Kiselev et al found that LF oscillations in PPG that lag LF HRV is likely to have a neurogenic nature, whereas HRV changes driven by LF PPG changes are likely to have a hemodynamic nature (due to cardiac output) (Kiselev et al, 2020).…”
Section: Ppg-derived Vascular Measuresmentioning
confidence: 99%